2022
DOI: 10.1096/fj.202200269rr
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structures: Associated multiple immune cells and analysis their formation in hepatocellular carcinoma

Abstract: The prognostic value of immune cells in tertiary lymphoid structures (TLSs) remains unclear in hepatocellular carcinoma (HCC). Here, 59 of 145 patients had TLSs in training set, 48 of 120 patients had TLSs in testing set. Immunohistochemistry (IHC) were used to label CD3+ T cells, CD20+ B cells, CD8+ T cells, CD208+ dendritic cells, and CD21+ follicular dendritic cells in TLSs. High CD20+, CD208+, and CD8+ cell densities were favorable prognostic factors for overall survival (OS). High CD3+, CD20+, CD208+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Immunohistochemical analysis revealed that high CD20 + , CD208 + and CD8 + cell densities in HCC patients were favourable prognostic factors for overall survival. In contrast, high CD3 + , CD20 + , CD208 + and CD8 + cell densities were significantly associated with a reduction in early recurrence 116 . The differences in these results may be related to the study population, sample size, statistical methods, criteria for TLS identification, TLS heterogeneity and location.…”
Section: Associations Of Tertiary Lymphoid Structures With Hccmentioning
confidence: 89%
See 1 more Smart Citation
“…Immunohistochemical analysis revealed that high CD20 + , CD208 + and CD8 + cell densities in HCC patients were favourable prognostic factors for overall survival. In contrast, high CD3 + , CD20 + , CD208 + and CD8 + cell densities were significantly associated with a reduction in early recurrence 116 . The differences in these results may be related to the study population, sample size, statistical methods, criteria for TLS identification, TLS heterogeneity and location.…”
Section: Associations Of Tertiary Lymphoid Structures With Hccmentioning
confidence: 89%
“…In contrast, high CD3 + , CD20 + , CD208 + and CD8 + cell densities were significantly associated with a reduction in early recurrence. 116 The differences in these results may be related to the study population, sample size, statistical methods, criteria for TLS identification, TLS heterogeneity and location.…”
Section: Relationship Between Tls and Prognosis Of Hccmentioning
confidence: 99%
“…We performed a large-scale study of LR-HCC and C-HCC by analysing and comparing the clinicopathologic and molecular characteristics using proteomic analysis. Although there were previous reports highlighting the favourable prognostic effect of TLS in HCC, 12,[40][41][42] study cohorts were not histologically categorized into HCC subtypes including LR-HCC. In our findings, although LR-HCC showed a significant correlation to larger tumour size and higher ES grade compared to the C-HCC of similar disease stage, survival analysis revealed significantly better OS and RFS in LR-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contradict the earlier conclusions. With an increased understanding of TLS, attention has been directed toward the maturity of TLS, revealing that mature TLS is linked to better cancer prognosis ( 49 ).…”
Section: Clinical Value Of Tlsmentioning
confidence: 99%